Website-Based National University Lecturer Payroll Process System Design: Website-Based National University Lecturer Payroll Process System Design - Haris Amanullah; Septi Andryana; Aris Gunaryati (Institute of Computer Science (IOCS), 2020)
The study discusses the making of a system for processing lecturer salaries, currently, payroll at the National University is carried out using an offline payroll system for calculating lecturer salaries, the existing system at the National University is actually optimal in conducting lecturer salaries, but still has shortcomings because it is not can be done online, especially in situations pandemic covid 19 like this which are recommended for wfh (work from home) by the government, but the admin at the bsdm must keep coming to work, therefore the author aims to create a website-based payroll system using PHP Framework Codeigniter (CI) and Mysql database, which can facilitate the admin to do the payroll process that can be done anywhere and anytime.